Nuclear physics - Devanathan, V (New Delhi: Narosa Publishing House, 2011)
Designed as a textbook for graduate students deals with the size, shape and properties of nuclei, the electric and magnetic moments, the strong nuclear force that binds nucleons, the nuclear structure, various nuclear models - the shell model, Nilsson's model, the collective model and unified model - radioactive decays such as the alpha, beta and gamma decays, nuclear and heavy ion reactions and synthesis of transuranic elements. The Strutinsky shell correction, the effect of parity violation in weak interaction, elementary particle interactions with nuclei and the quark structure of the nucleon are also briefly discussed.
Appendix A-H 357-401p.; Subject Index 402-406p.
Keywords: Nuclear physics; Physics